The therapeutic potential of wogonin observed in preclinical studies - Sharifi-Rad, Javad (2021)
Wogonin is a flavonoid found in different plants such as roots of Scutellaria baicalensis Georgi distributed mainly in Asia and Europe. Dried root extracts of S. baicalensis with high content of wogonin, popularly known as "Huang-Qin" or Chinese or baical skullcap, have been used for long time in traditional Chinese medicine. Several health benefits are attributed to wogonin and derivatives showing anti-inflammatory, antiviral, anticancer, and antioxidant effects and more recently antineurodegenerative properties. Preclinical pharmacological activities of wogonin against diverse types of cancer such as breast, colorectal, and human gastric cancer will be presented in this review. In addition, studies on oxidative stress and bioavailability of wogonin will be discussed together with antineurodegenerative potential with special focus on Alzheimer's disease. Outcomes extracted from the last preclinical studies related to therapeutic applications of wogonin will be commented and updated in this review. The scientific evidence collected in this review aims to encourage transfer of the preclinical evidence of wogonin to new clinical studies.